Lymphography technique for detecting metastasis in canine malignancies - Anjan Kumar Sahoo (International Journal of Veterinary Science and Research - Peertechz Publications, 2023)
Cancer in animals and human beings spread through both hematogenous and lymphatic routes. While detection of cancer through the hematogenous route is easy delineating the different pathways in lymphatic and lymph nodes involves skill and an advanced imaging system. The present review highlights different techniques for outlining the lymphatic in canine cancer patients. The Sentinel Lymph Node (SLN) is the first or echelon or initial draining node from the primary tumor mass in a regional lymphocentre. Positive (SLN) needs to be evaluated, and surgical planning for its removal along with local tumor control affects the prognosis of any carcinoma or sarcoma. This review discusses different indirect lymphography procedure and their importance to detect the sentinel lymph node in a lymphatic basin both preoperatively and intraoperatively for better surgical assessment of various canine malignancies.